Structural investigations of phosphorus-nitrogen compounds.: 5.: Relationships between molecular parameters of 2,2-diphenyl-4,6-cis-oxytetra(ethyleneoxy)-4,6-R2-cyclotriphosphazatrienes (R = Cl, OCH2CF3, OPh, OMe, NHPh, NHBut) and substituent basicity constants - Besli, S; Coles, SJ; Davies, DB; Hursthouse, MB; Kiliç, A; Mayer, TA; Shaw, RA (Blackwell Munksgaard, 2002)
A systematic study of the products of nucleophilic substitution reactions of cis-ansa N3P3Ph2[O(CH2CH2O)(4)]Cl-2 (3) is reported. These reactions give a number of new structures with the general formula N3P3Ph2[O(CH2CH2O)(4)]R-2 [where R=OCH2CF3 (4), OPh (5), OMe (6), NHPh (7.H2O), NHBut ( 8)]. A comparison has been made between the sum of the substituent basicity constants, Sigmaalpha(R), that are obtained in nitrobenzene solution and eight molecular parameters of the N3P3 ring [the P-N bond lengths a, b, c; the internal bond angles alpha, beta, gamma, delta; and the difference between the bond lengths a and b, Delta(P-N)]. It is found that the systematic changes in the molecular parameters of (3)-(8) are in line with changes in alpha(R) values. This result implies the similarity in relative electron-releasing capacity of substituents R in the solid state and in solution.
Keywords: Crystal-Structure; Derivatives; Complex; Ether